Transformasi Agen Brilink dari Mitra Menjadi Wirausahawan Mandiri di Kabupaten Kerinci Menggunakan Pendekatan Model Adkar - Boni Wijaya; Zulfina Adriani; Ade Perdana Siregar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This research uses a qualitative approach with a case study research type to understand in depth the transformation process of BRILink Agents from banking partners to independent entrepreneurs in Kerinci Regency. Research informants were selected purposively and consisted of 10 BRILink Agents who actively run their businesses. Primary data were obtained through observation and in-depth interviews arranged based on the ADKAR Model components, namely Awareness, Desire, Knowledge, Ability, and Reinforcement. Secondary data were obtained from documentation and data on the number of BRILink Agents available at BRI and other supporting documents. The data analysis technique used the interactive model of Miles, Huberman, and Saldaña which includes three stages: data reduction, data presentation, and drawing conclusions. In the data reduction stage, the results of interviews and observations were classified based on the five ADKAR components. Next, the data were presented in the form of a thematic narrative to identify the transformation patterns experienced by BRILink Agents. The final stage was carried out through drawing and verifying conclusions to gain a comprehensive understanding of the factors that drive the transformation of BRILink Agents into independent entrepreneurs.